The Psychological Effects of Delayed Laboratory Results on Patients and Nurses - Yahya, Alhamzi, Nasser; Ghazi, Almaliki , Abdullah; Ahmad, Alsamel, Rsheed; Mukhlef, Alanazi, Faisal; Saleh, Alsubaie, Mohamad (Journal of Posthumanism, 2025)
Delays in laboratory testing and the subsequent reporting of results represent a significant, yet often overlooked, stressor within the healthcare ecosystem. This systematic review synthesizes current literature to explore the multifaceted psychological impact of these delays on both patients awaiting diagnoses and nurses operating at the clinical frontline. For patients, delayed results are a potent source of anxiety, uncertainty, and a prolonged state of hypervigilance, which can exacerbate their overall distress and impair coping mechanisms. For nurses, systemic delays contribute to increased cognitive load, moral distress, and emotional exhaustion, as they navigate the tension between patient expectations and operational limitations. These delays are frequently intertwined with workflow inefficiencies, communication breakdowns, and high-stress clinical environments, further compounding psychological strain. This paper argues that delayed laboratory results are not merely an operational issue but a critical psychosocial determinant affecting care quality and workforce sustainability. By examining the evidence through the lenses of anxiety, burnout, and professional self-efficacy, this review highlights the urgent need for diagnostic stewardship, enhanced communication strategies, and systemic support mechanisms to mitigate these adverse psychological effects and foster a more resilient healthcare environment.